Multifractal Behaviors of Daily Temperature Time Series Observed over Benin Synoptic Stations (West Africa) - AGBAZO, Médard Noukpo; KOTO NGOBI, GABIN (My University, 2019)
In this study, Multifractal Detrended Fluctuation Analysis (MFDFA) is applied to daily temperature time series in Benin synoptic stations from 1967 to 2012. The purpose is to examine the degree of multifractality and compare multifractal characteristics of temperature in various climatic areas (subequatorial and Sudanian). The analysis reveals that the daily temperature time series shows a multifractal behavior that is sensitive to the station’s geographic position and presents a positive long-term correlation. Weather conditions and the geographic position of the synoptic stations affect the shape and the characteristics of temperature spectrum. The multifractality is stronger in subequatorial region than the Sudanian. The major source of multifractality in temperature series is found to be the fat-tailed probability density function. However, long-range correlations also partly contribute to the multifractal features. Except Kandi’s synoptic station, the spectrum is left-skewed. The findings indicate the usefulness of the non-linear analysis in climate research due to the complex interactions among the natural processes. It can help understand the mechanisms governing the dynamics of temperature time series in Benin.
Keywords: Benin; scaling exponent; MFDFA; singularity spectrum; temperature; nonlinear dynamics.